Optimizing the Performance of Bhabinkamtibmas in Preventing the Crime of Motor Vehicle Theft in the Jurisdiction of Polres Brebes - Tamboto, Ezra Aryaguna (Advances in Police Science Research Journal, 2024)
This study aims to determine the organizational resources of the Bhabinkamtibmas Unit in supporting performance, preventing criminal acts of motorized vehicle theft, and finding out the Bhabinkamtimas work system and methods. The type of research used is a type of field research. Data collection techniques are interview techniques, observation techniques (Observation), and documentation studies. The analysis techniques used in this study include (1) data reduction, namely selecting data that is related to problems regarding the performance of Bhabinkamtibmas, (2) presenting data, namely analyzing the performance of Bhabinkamtibmas in preventing criminal acts of theft systematically, (3) drawing conclusions or verification, namely drawing a conclusion from the research results in the data that has been presented. The results of this study were (1) it was found that the performance of the Bhabinkamtibmas Polres Brebes in preventing motorbike theft was not optimal. For example: in carrying out tasks, the competence of human resources is not optimal. There are no innovations in the implementation of activities. And also the lack of direct supervision from the leadership. (2) Many obstacles and deficiencies are found in the performance of Bhabinkamtibmas, so efforts to prevent the crime of motorized vehicle theft are not optimal.